Next generation mobile networks and ubiquitous computing - Pierre, Samuel (Premier reference source, 2011)
"This book provides a comprehensive and unified view of the latest and most innovative research findings on the many existing interactions between mobile networking, wireless communications, and ubiquitous computing" - Provided by publisher